Role of embolization in surgery for skull base tumors - D. A. Gulyaev; I. Yu. Belov; I. A. Kurnosov; K. A. Chizhova; N. K. Samochernykh; P. V. Balakhnin (Сибирский онкологический журнал, 2025)
Objective: to summarize global and personal experience in the application of embolization techniques in the surgical management of benign and malignant skull base tumors, comprehensively analyzing associated risks and complications to improve treatment approaches and minimize negative outcomes. Material and Methods. An analysis of scientific publications from international medical databases (PubMed, Cochrane Library, Elibrary and others) covering studies over the past 20 years, as well as a retrospective analysis of our own clinical data on embolization for skull base tumors was conducted. Specific details and features of embolization techniques, materials used, and criteria for complication assessment, including classifications developed by international expert societies, were thoroughly examined. Results. The analysis revealed that outcomes from embolization techniques in skull base tumor surgery remain controversial, with a wide range of complications from minor reactions to severe and disabling conditions. Major complications identified included stroke, cranial nerve dysfunction, tissue necrosis, and death. Determination of the optimal timing interval between embolization and subsequent surgical resection is critical, as premature surgery does not fully exploit embolization potential, whereas delayed surgery increases the risk of recanalization and progression of perifocal edema, exacerbating neurological deficits. Particular attention was given to the postembolization neurological syndrome (PENS), which may result in persistent and irreversible neurological impairment. Conclusion. Despite potential benefits in reducing intraoperative blood loss and facilitating surgical procedures, the use of embolization technologies requires careful evaluation of risks and potential complications. Decisions regarding embolization should be individualized and based on a multidisciplinary approach considering the specifics of each clinical case.